2018
DOI: 10.1038/s41598-017-18915-5
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of common Gram-negative pathogens using a highly multiplexed high resolution melt curve assay

Abstract: The identification of the bacterial species responsible for an infection remains an important step for the selection of antimicrobial therapy. Gram-negative bacteria are an important source of hospital and community acquired infections and frequently antimicrobial resistant. Speciation of bacteria is typically carried out by biochemical profiling of organisms isolated from clinical specimens, which is time consuming and delays the initiation of tailored treatment. Whilst molecular methods such as PCR have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…HRM assays have been widely used to detect gene mutations [ 43 45 ]. However, for G6PD genotyping, most of the developed HRM assays are singleplex or duplex, which can only detect one or two mutations simultaneously [ 38 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HRM assays have been widely used to detect gene mutations [ 43 45 ]. However, for G6PD genotyping, most of the developed HRM assays are singleplex or duplex, which can only detect one or two mutations simultaneously [ 38 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, after PCR amplification, an additional gel electrophoresis step is required to check the size of the amplified PCR products, which is impractical for large population screening. The HRM assay is a powerful and reliable tool that has been widely used in the detection of gene mutations [ 43 45 ]. Previously, HRM assays were applied to detect G6PD mutations in different population groups [ 38 , 46 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a study in Uganda reported that K. pneumoniae (52%) and E. coli (44%) were the most frequent Gram-negative organisms from patients' clinical specimens [17]. As well, global studies proved that infections caused by Gram-negative bacteria are predominant compared to other pathogens [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…We report here the design of an RT-PCR assay to detect chloramphenicol susceptibility in E. coli and Klebsiella spp. employing high-resolution melt (HRM) analysis, which enables a high degree of multiplexing, without expensive fluorescent probes 22 …”
Section: Introductionmentioning
confidence: 99%